Torque Limit-Based Inertial Control of a DFIG for Rapid Frequency Stabilization - Yien Xu (Frontiers Media S.A., 2021)
With the increasing penetration of renewable energy generation, the frequency stability of a power grid can be significantly threatened. A doubly-fed induction generator (DFIG) participates in the frequency support of a power grid by releasing kinetic energy (KE) to boost the frequency nadir (FN). However, during rotor speed restoration, it is difficult to counterbalance the size of a second frequency drop (SFD) and the rotor speed recovery duration. This paper proposes an improved torque limit-based inertial control (TLBIC) to raise the FN by releasing less kinetic energy while guaranteeing rapid frequency stabilization with reduced SFD. To this end, when detecting a disturbance, the DFIG enhances the active reference power to the torque limit, and then the active power reduces smoothly based on an exponential function until the maximum power point tracking (MPPT) curve is met, and the rotor speed reverts to the initialization operating condition along the MPPT curve. A simulation system model with various wind power penetrations is established in EMTP-RV. Results show that the proposed scheme boosts the FN at a high level with less KE and guarantees rapid frequency stabilization.